Proceedings of the SIGCHI Conference on Human Factors in Computing Systems the CHI Is the Limit - CHI '99 1999
DOI: 10.1145/302979.303143
|View full text |Cite
|
Sign up to set email alerts
|

FotoFile

Abstract: FotoFile is an experimental system for multimedia organization and retrieval, based upon the design goal of making multimedia content accessible to non-expert users. Search and retrieval are done in terms that are natural to the task. The system blends human and automatic annotation methods. It extends textual search, browsing, and retrieval technologies to support multimedia data types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The concept of automatic labelling of photos has a great influence in fields of face recognition and object detection (Cui et al, 2007). Ultimately users can verbally annotate photographs or record the accompanying audio (Kuchinsky et al, 1999). It is noteworthy that most of the developed systems have not been evaluated in terms of the difficulty of PIM evaluations (Elsweiler and Ruthven, 2007) and hence the problems remain unsolved that may affect the refinding of information in general and photographs in particular.…”
Section: Why Personal Photographsmentioning
confidence: 99%
“…The concept of automatic labelling of photos has a great influence in fields of face recognition and object detection (Cui et al, 2007). Ultimately users can verbally annotate photographs or record the accompanying audio (Kuchinsky et al, 1999). It is noteworthy that most of the developed systems have not been evaluated in terms of the difficulty of PIM evaluations (Elsweiler and Ruthven, 2007) and hence the problems remain unsolved that may affect the refinding of information in general and photographs in particular.…”
Section: Why Personal Photographsmentioning
confidence: 99%
“…This leads to more and more personal digital photos being shared online for browsing and retrieval. As collections grow rapidly, so does the demand for searching, browsing and organising of digital photos (Kuchinsky et al , 1999). Therefore, it is necessary to organise these digital photos effectively.…”
Section: Introductionmentioning
confidence: 99%
“…1. More relevant tags are needed: As previously explained, users do not typically label their personal images and when they do, they tend to do it in "bulk" [71]. Moreover, sometimes the tags do not describe the image contents [65].…”
Section: Discussion and Implications For Designmentioning
confidence: 99%
“…One of the main problems with these tag based search interfaces is that not all tags describe the actual content of the media [65], and therefore tags can only help find the content that has been correctly tagged. Actually, Kuchinsky et al [71] found that most of the times full collections or folders are assigned the same tags, making it hard to find specific images in the collection. This fact allows for image/video analysis techniques to enhance the search and retrieval user experience, research field that has shown great activity recently [107,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation